2022
DOI: 10.1002/adfm.202110674
|View full text |Cite
|
Sign up to set email alerts
|

High‐Voltage Aqueous Mg‐Ion Batteries Enabled by Solvation Structure Reorganization

Abstract: Herein, an eco‐friendly and high safety aqueous Mg‐ion electrolyte (AME) with a wide electrochemical stability window (ESW) ≈3.7 V, containing polyethylene glycol (PEG) and low‐concentration salt (0.8 m Mg(TFSI)2), is proposed by solvation structure reorganization of AME. The PEG agent significantly alters the Mg2+ solvation and hydrogen bonds network of AMEs and forms the direct coordination of Mg2+ and TFSI‐, thus enhancing the physicochemical and electrochemical properties of electrolytes. As an exemplary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 51 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…In addition, H 2 O molecules can connect to each other and form a network through H bonds. The H 2 O–H 2 O interaction network will be disrupted upon the addition of salts or organic solvents, which can be attributed to the additional interaction of H 2 O with anions or solvent molecules. For instance, Chang et al proposed an aqueous hybrid electrolyte containing ethylene glycol (EG) solvents. EG can not only interact with Zn 2+ but also form the H bond with H 2 O to weaken the Zn 2+ –H 2 O interaction, affording the electrolyte with a low freezing point and reversible Zn deposition/stripping …”
Section: Electrolyte Microstructuresmentioning
confidence: 99%
“…In addition, H 2 O molecules can connect to each other and form a network through H bonds. The H 2 O–H 2 O interaction network will be disrupted upon the addition of salts or organic solvents, which can be attributed to the additional interaction of H 2 O with anions or solvent molecules. For instance, Chang et al proposed an aqueous hybrid electrolyte containing ethylene glycol (EG) solvents. EG can not only interact with Zn 2+ but also form the H bond with H 2 O to weaken the Zn 2+ –H 2 O interaction, affording the electrolyte with a low freezing point and reversible Zn deposition/stripping …”
Section: Electrolyte Microstructuresmentioning
confidence: 99%
“…[23,27] Similarly, as seen in Figure 2c, the 1 H NMR chemical shift of H 2 O decreased in the presence of PEG, which can be attributed to the increase in electron density around the H atom due to the hydrogen bonding between the O atom in PEG and the H atom in H 2 O. [24] The above results indicate that PEG is an excellent molecular crowding agent for reducing the activity of water molecules, and the P50 electrolyte has the best physical and chemical properties and, as such, may be a promising electrolyte for low-cost SCs devices. As Figure S4 shows, through DFT-MD simulations, we found that there were a large number of free water molecules in 8 m NaClO 4 , which form a hydrogen bonding network with each other.…”
Section: Chemelectrochemmentioning
confidence: 57%
“…The PEG agent was able to significantly alter the Mg 2 + solvation and hydrogen bonds networks of Mg-ion batteries, improving the OVW and other physical and chemical properties of the Mg-ion electrolyte. [24] This was because the molecular crowding effect of PEG was able to change the hydrogen-bonding structure of water, reducing its activity and inhibiting its decomposition. The above studies demonstrated the great potential of PEG in aqueous Li-ion, Zn-ion, and Mgion batteries and also inspired us to hypothesize that PEG must have a similar effect when acting as an electrolyte additive for SCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 110 cycles, the capacity retention ratio of the CVOH microspheres is 75%, which is quite high for V‐bearing cathode materials storing Mg‐ion in aqueous three‐cathode configuration; the capacity loss is due to the slight dissolution of cathode material into the excessive electrolyte solution. [ 4,19 ] The coulombic efficiencies are stable at ≈100% during these 110 cycles. These results indicate that the insertion/extraction process of Mg 2+ ions in CVOH microspheres is highly reversible while the CVOH cathode is highly stable during the discharging/charging process.…”
Section: Resultsmentioning
confidence: 99%